Exploration of the Development City Branding Spirit of Majapahit in Encouraging Creative Economic Growth of MSMEs in Mojokerto City - Putri, Salsabilla; Mukhlis, Imam (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2024)
Becoming more severe at the area and public level should be noticeable as a technique for creating money-related improvement and dealing with people's association help. Subsequently, the Mojokerto Territorial Government should zero in on the circumstance with a nearby advancement extraordinary framework. The control of connecting and resource-based potential in planning is primary for work on the chance of neighbourhood improvement execution. Vigilant arrangements with the heading of nearby improvements end up being more effective. This article will isolate the Advancement of City Checking Soul of Majapahit in Associating with the Creative Money-related Progress of MSMEs in Mojokerto City. This assessment uses an exciting evaluation, where data is taken from the working environment of cooperatives, MSMEs, industry, and trade in Mojokerto City. The triangulation analysis method used in this research and Miles and Matthew’s interaction pattern analysis, which takes place continuously through collecting, reducing, presenting data, and conclusions, will ensure good data generation. This study shows that the success of the Mojokerto City Government in building a creative economy with local innovation and carrying the "Spirit of Majapahit" branding has a positive impact on the growth of the creative economy because local MSMEs contribute by producing a variety of interesting products that support the "Spirit of Majapahit" branding ranging from consumption needs to handicrafts.